Contribution of Bamboo for Vibratory Comfort in Biomechanics of Cycling (2017)
Vibrations in cycling produced by road irregularities could cause health problems and affect the cyclist’s comfort and performance. Therefore researchers and manufacturers focus their efforts to reduce the vibrations.